High-performance flexible hydrogen sensor made of WS2 nanosheet–Pd nanoparticle composite film. (4th April 2016) - Kuru, Cihan; Choi, Duyoung; Kargar, Alireza; Liu, Chin Hung; Yavuz, Serdar; Choi, Chulmin; Jin, Sungho; Bandaru, Prabhakar R
Abstract: We report a flexible hydrogen sensor, composed of WS2 nanosheet–Pd nanoparticle composite film, fabricated on a flexible polyimide substrate. The sensor offers the advantages of light-weight, mechanical durability, room temperature operation, and high sensitivity. The WS2 –Pd composite film exhibits sensitivity ( R 1 / R 2, the ratio of the initial resistance to final resistance of the sensor) of 7.8 to 50 000 ppm hydrogen. Moreover, the WS2 –Pd composite film distinctly outperforms the graphene–Pd composite, whose sensitivity is only 1.14. Furthermore, the ease of fabrication holds great potential for scalable and low-cost manufacturing of hydrogen sensors.